Recovery of low concentration ammoniacal nitrogen from aquaculture wastewater using oil palm fiber biochar - Ahmad, Tanveer (2023)

(untitled)
The existence of ammonia-nitrogen (NH3-N) in water bodies has received much attention due to its toxicity and its impact on human health and the environment. Aquaculture wastewater (AQW) contains NH3-N, and this can cause tissue damage or even death of fishes. Nevertheless, NH3-N is also categorized as a nutrient and a source of nitrogen in fertilizer. Adsorption process is considered one of the promising techniques for the adsorption of NH3-N. Recently, various sorbents have been used for NH3-N treatment, however limited studies were reported on biochar as a sorbent for NH3-N recovery in low concentration. Most the studies reported on synthetic wastewater and for the removal of high concentrations of NH3-N (> 5ppm). In this study, the feasibility of oil palm fiber (OPF) biochar on the recovery of NH3-N was investigated. The OPF biochar was prepared in the presence of N2 (pyrolysis) or air (partial oxidation). The preparation was also tested for physically and chemically activated. Design of experiments (DOE) was used to optimize the biochar preparation process. Upon optimization, process study, thermodynamics, kinetics, and mechanism of the removal process was deduced using various parameters and models. Finally, a cost analysis was made to understand the economic viability of the product produced. The OPF biochar preparation was deduced as 300 °C, 150 min, and 100 ml air/min by DOE. The best biochar prepared with air injection shows a removal efficiency of 71.6 % and capacity of 1.6 mg/g for NH3-N in synthetic wastewater. Further activation of biochar did not improve the removal efficiency. The process study was further optimized, and the following was achieved; contact time (180 min), shaking speed (150 rpm), dosage (2 g), pH 8~9, and temperature (25 °C). The best removal efficiency adsorption capacity achieved at above conditions are 72.6 % and 0.4 mg/g respectively in actual AQW. The isotherm data of NH3-N agreed well with Linear and non-Linear Freundlich model (R2 = 0.9009, 0.9518) compared to Langmuir model (R2=0.8794, 0.9303) respectively, show heterogenous nature of the OPF biochar. The Langmuir adsorption capacity is 6.42 mg/g for the OPF biochar using non-Linear model. In the kinetics study, the best R2 values were 0.9988, and 0.9950 for Linear and non-Linear pseudo second order as compared to pseudo first order (R2 = 0.9861, and 0.9843), respectively, which indicates that chemisorption is the dominant mechanism. The results of the Intra-particle diffusion model indicate that the intraparticle diffusion is not the only rate-limiting step and shows strong initial adsorption as the Ri (0.47) is between 0.5 > Ri > 0.1. Based on the temperature effect, the values of Gibbs free energy (ΔG°) for OPF biochar were in the range of -13.83 to - 15.38 kJ/mol. The negative value of ΔG° shows that adsorption is spontaneous. The entropy (ΔS°) value (102.72 J/mol) suggests that randomness increases during the adsorption process. The positive value (16.90 kJ/mol) of the enthalpy change (ΔH°) reveals that the process is endothermic and the adsorption efficiency of NH3-N increases with increasing temperature. In the AQW, OPF biochar exhibits selective iv recovery of NH3-N. The characterization of the OPF biochar shows that the ion exchange process occurs during NH3-N recovery, however, oxygen surface functional groups also play a key role. The cost analysis of the OPF biochar was investigated using a pilot plant design. The optimize biochar is cost effective and the price is RM 2.17/kg comparable to the ones reported in literature and commercially available. Biochar is an environmentally friendly and biodegradable sorbent. It is suggested in future, the spent OPF biochar can be further utilized as a soil conditioner or fertilizer.